A review of the biology and literature of the Gulf Coast Toad (Incilius nebulifer), native to Mexico and the United States - Mendelson, Joseph R. Iii; Kinsey, Chase. T.; Murphy, James. B. (Zootaxa, 2015)
The Gulf Coast Toad (Incilius nebulifer) is an abundant and widespread species within its range in the United States and Mexico, so it appears on many faunal checklists and is considered in diverse kinds of research. We review the basic biology, distribution, and published history of this species, identifying only those records and publications referable to I. nebulifer, to help researchers identify published works pertaining to I. nebulfer rather than I. valliceps, with which it formerly was considered to be conspecific.